Repellent activity of plants from the genus Chenopodium to Ostrinia nubilalis larvae - Dariusz Piesik; Didier Rochat; Jan Bocianowski; Frédéric Marion-Poll (Plant Protection Science, 2018)
The olfactory choices expressed by naïve neonate European corn borer (ECB) larvae were tested by recording their locomotor activities in response to odours coming from plants of the genus Chenopodium (producing phytoecdysteroids or not). ECB larvae were found to be repelled from phytoecdysteroid-positive species, except C. album and C. polyspermum. On the contrary, they were mildly attracted or mildly repelled by phytoecdysteroid-negative species, except C. botrys (which emits a rancid odour). These observations indicate that neonate ECB larvae clearly differentiate plant odours and suggest that well-defended plants may emit repellent odours.